Parental Caregiving Experiences in Epidermolysis Bullosa: A Phenomenological Study. - Khalili, Hassan; Moonaghi, Hossein Karimi; Kianifar, Hamid Reza; Manzari, Zahra Sadat (International Journal of Community Based Nursing & Midwifery, 2025)
Background: Epidermolysis bullosa (EB) is a rare, inherited disease characterized by mucocutaneous fragility. It requires continuous family support and caregiving. However, insights into the complex realities of daily caregiving roles for parents remain limited. This study aimed to explore the lived experiences of Iranian family caregivers caring for their children with EB. Methods: This phenomenological study was carried out from February to November 2023 at Mashhad Akbar Hospital or participants' homes. Purposeful maximum variation sampling was used to recruit 10 parents (3 fathers, 7 mothers) who met the inclusion criteria. Data were gathered through in-person, semi-structured interviews and analyzed using Van Manen method in MAXQDA software version 2020. Results: Caregivers' experiences elucidate the profound adversity endured by parents raising children with EB. Four themes emerged from the data: "lost and confused about care and treatment"; "trapped in endless cycle of hardship caring"; "inevitable self-isolation"; and "bitter and deteriorating family life". Conclusion: Family caregivers who provide care for children with EB face numerous difficulties, leading to significant stress and heavy responsibilities. Their lived experiences provide a comprehensive picture of the physical, psychological, and social difficulties related to this rare disease.